Novel quinazolin-4(3H)-one bionic-alkaloids bearing an 1,3,4-oxadiazole fragment as potential fungicides inhibiting Botrytis cinerea: Design, synthesis and bioactive-guided structural optimization - Xiaobin Wang; Lili Yan; Juan Zhang; Yilin Zhang; Zongqun Zhang; Quanqing Zhao; Qingfang Cheng; Weihua Zhang (Arabian Journal of Chemistry, 2024)
The ever-rising resistance in Botrytis cinerea has appeared as the awkward agricultural challenge that could be effectively resolved by developing novel fungicides featuring disparate action mechanisms. Aiming to explore novel fungicidal leads inhibiting B. cinerea, quinazolin-4(3H)-one bionic-alkaloids bearing an 1,3,4-oxadiazole fragment were conceived, synthesized, and systematically optimized under the guidance of anti-B. cinerea activities. The aforementioned optimization on molecular structures generated the anti-B. cinerea candidate I25 owning the promising in vitro EC50 value (0.76 μg/mL) that was fantastically superior to those of boscalid, penthiopyral, pyrimethanil and imazalil (0.86, 1.03, 15.91 and 2.15  µg/mL). Whereafter, the in vivo anti-B. cinerea preventative efficacy of an active molecule I25 was noticeably evaluated as 69.3 % at 200 µg/mL, which was megascopically better than that of boscalid (60.6 %). Furthermore, the preliminary investigation on action mechanisms indicated that the fungicidal molecule I25 could induce the conspicuous wrinkle on hyphal surfaces and increase the membrane permeability of B. cinerea cells. The above results have emerged as an imperative reference to developing the novel fungicides that could effectively control gray mold caused by B. cinerea.